2008
DOI: 10.1182/blood-2008-06-165738
|View full text |Cite
|
Sign up to set email alerts
|

Elevated growth differentiation factor 15 expression in patients with congenital dyserythropoietic anemia type I

Abstract: Congenital dyserythropoietic anemia (CDA) is a rare group of red blood cell disorders characterized by ineffective erythropoiesis and increased iron absorption. To determine whether growth differentation factor 15 (GDF15) hyper-expression is associated with the ineffective erythropoiesis and iron-loading complications of CDA type I (CDA I), GDF15 levels and other markers of erythropoiesis and iron overload were studied in blood from 17 CDA I patients. Significantly higher levels of GDF15 were detected among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 14 publications
4
95
1
2
Order By: Relevance
“…Iron loading may be alleviated by ongoing iron loss, such as menstrual bleeding or pregnancies. The study by Tamary on iron overload pathogenesis in CDA I patients supports the notion that high levels of GDF15 contribute to this pathology that, 44 because of its overexpression, occurs together with ineffective erythropoiesis and positively correlates with ferritin levels in adults. In 2011, Casanovas demonstrated that serum hepcidin to ferritin ratio is strongly decreased in CDA patients compared to control subjects; thus showing that serum hepcidin concentrations are inappropriately low.…”
Section: Complications and Therapeutic Approachessupporting
confidence: 54%
See 1 more Smart Citation
“…Iron loading may be alleviated by ongoing iron loss, such as menstrual bleeding or pregnancies. The study by Tamary on iron overload pathogenesis in CDA I patients supports the notion that high levels of GDF15 contribute to this pathology that, 44 because of its overexpression, occurs together with ineffective erythropoiesis and positively correlates with ferritin levels in adults. In 2011, Casanovas demonstrated that serum hepcidin to ferritin ratio is strongly decreased in CDA patients compared to control subjects; thus showing that serum hepcidin concentrations are inappropriately low.…”
Section: Complications and Therapeutic Approachessupporting
confidence: 54%
“…Molecular mechanisms of iron overload have been recently characterized. 43,44 In both conditions, iron loading is not dependent on transfusions (but could be increased by them). Iron loading may be alleviated by ongoing iron loss, such as menstrual bleeding or pregnancies.…”
mentioning
confidence: 99%
“…Ferritin is increased in iron overload secondary to chronic blood transfusions irrespective of the reason and also in the so called iron loading anemias, which include beta-thalassemia syndromes 8 and congenital sideroblastic or dyserythropoietic anemias, 9 characterized by high levels of ineffective erythropoiesis and low hepcidin production. All these conditions are usually well known from the patient's history and may be diagnosed by specific tests.…”
Section: Clara Camaschella and Erika Poggialimentioning
confidence: 99%
“…4 Furthermore, GDF15 concentrations are strongly increased in disorders hallmarked by increased ineffective erythropoiesis, such as β-thalassemia, congenital dyserythropoietic anemias or, to a lesser extent, pyruvate kinase deficiency. [4][5][6][7] GDF15 is expressed in several organs, including liver, lung, kidney, and exocrine glands. 8,9 In mice, GDF15 acts as a cardioprotective factor released by the myocardium, and as a neurotrophic factor for midbrain dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%